Preferences and satisfaction of artificial lighting in Malaysian shop office/ Tan Hui Ping and Roshida Abdul Majid - Tan, Hui Ping; Abdul Majid, Roshida (Universiti Teknologi MARA, Perak, 2023)
The work environment significantly impacts the productivity of office workers. A healthy and comfortable workspace is essential to achieve positive outcomes in a stressful environment. By investigating the lighting preferences and satisfaction levels of office workers in intermediate shop offices in Malaysia, this study aims to improve the quality of workplace environments by enhancing the properties of artificial lighting and its effects on employee performance. This study focuses on the intermediate shop office, a popular office type in Malaysia that often has poor lighting. Most intermediate shop offices are long and narrow, with windows only at the front and rear of the shops. Good daylight design can save up to 75% of the energy used for electric lighting. However, natural lighting is an uncontrollable source that can cause glare and visual discomfort for office workers using VDTs. Therefore, artificial lighting plays an important role in increasing visual comfort in Malaysian intermediate shop offices. Questionnaires were distributed to office occupants in intermediate shop offices, and significantly lower satisfaction levels were found in the lighting properties and working environment. The average level of illuminance satisfaction among office workers was 2, which is below average. Meanwhile, the correlated colour temperature satisfaction level was approximately 1.29. According to 41% of respondents, the colour temperature in their current office was 3000k, and the satisfaction levels for the number of illuminances and lighting type were 1.83 and 1.66, respectively. These findings indicate a need to improve the lighting conditions in Malaysian intermediate shop offices.